2014
DOI: 10.1111/adj.12221
|View full text |Cite
|
Sign up to set email alerts
|

Full-mouth scaling and root planing in type 2 diabetic subjects: one-year microbiological outcomes

Abstract: Background: This study evaluated the microbiological effects of full-mouth (FM) and partial-mouth (PM) scaling and root planing (SRP) in type 2 diabetic subjects with chronic periodontitis (ChP), up to 12 months. Methods: Thirty-four type 2 diabetic subjects with ChP received either FMSRP (n = 17), in two sessions within two consecutive days, or PMSRP (n = 17) in four sessions within 21 days. Six subgingival biofilm samples per subject were analysed by checkerboard DNA-DNA hybridization for 40 bacterial specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In light of treatment, it is important to note that the vast majority of the data available on the microbial effects of periodontal treatment (elimination/suppression postulate) were obtained using checkerboard DNA-DNA hybridization. This technique was used to determine the microbial shifts subsequent to scaling and root planing alone, 92,98,100,[171][172][173][174][175][176][177] with adjunctive local and /or systemic antimicrobials, 22,23,25,98,100,110,111,150,176,[178][179][180][181][182] , and surgical 23,181,183,184 and laser [185][186][187][188] increase in the proportions of Actinomyces species. 22,23,110,111 Because 16S sequencing allows the entire bacterial community to be studied simultaneously, rather than only a subset of pathogenic species, this created an unprecedented opportunity for ecological investigation of the periodontal microbiome.…”
Section: Tre Ating To Targ E T MI Crob Ial Succe Ssmentioning
confidence: 99%
See 1 more Smart Citation
“…In light of treatment, it is important to note that the vast majority of the data available on the microbial effects of periodontal treatment (elimination/suppression postulate) were obtained using checkerboard DNA-DNA hybridization. This technique was used to determine the microbial shifts subsequent to scaling and root planing alone, 92,98,100,[171][172][173][174][175][176][177] with adjunctive local and /or systemic antimicrobials, 22,23,25,98,100,110,111,150,176,[178][179][180][181][182] , and surgical 23,181,183,184 and laser [185][186][187][188] increase in the proportions of Actinomyces species. 22,23,110,111 Because 16S sequencing allows the entire bacterial community to be studied simultaneously, rather than only a subset of pathogenic species, this created an unprecedented opportunity for ecological investigation of the periodontal microbiome.…”
Section: Tre Ating To Targ E T MI Crob Ial Succe Ssmentioning
confidence: 99%
“…In light of treatment, it is important to note that the vast majority of the data available on the microbial effects of periodontal treatment (elimination/suppression postulate) were obtained using checkerboard DNA‐DNA hybridization. This technique was used to determine the microbial shifts subsequent to scaling and root planing, alone 92,98,100,171‐177 with adjunctive local and/or systemic antimicrobials, 22,23,25,98,100,110,111,150,176,178‐182 , and surgical 23,181,183,184 and laser 185‐188 approaches. Collectively, these studies demonstrated that the 40 bacterial species from the checkerboard panel serve as an excellent thermometer of treatment efficacy.…”
Section: Treating To Target Microbial Successmentioning
confidence: 99%
“…A total of 109 CP patients with T2DM and obesity, admitted in our hospital from November 2016 to November 2017 were the study participants. The inclusion criteria were: (1) eligibility for the diagnosis of chronic periodontitis [7]; eligibility for the diagnosis of type 2 diabetes mellitus (T2DM); (3) obesity with BMI > 28; (4) age > 18 years; (5) regular hypoglycemic treatment for diabetes for stable blood glucose control; and (6) signing of an informed consent. The exclusion criteria were: (1) remaining teeth < 20; (2) pregnant or lactating women; (3) periodontal therapy within three months before the study; and (4) intake of antibiotics within the previous one month.…”
Section: Experimental General Characteristics Of Subjectsmentioning
confidence: 99%
“…Chronic periodontitis increases levels of inflammatory factors and impedes glucose metabolism through insulin resistance (IR), thereby aggravating T2DM [4]. Type 2 diabetes mellitus impacts on oral flora, contributes to their attachment, and weakens the body's ability to fight infection, thereby exacerbating CP.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that patients with T2DM treated for periodontitis have reduced periodontopathic bacteria and improved glycemic control [22][23][24][25]. Patients with T2DM complicated by periodontitis have more red complex species, and poor glycemic control is thought to be associated with increased levels of red complex species in the oral cavity [26].…”
Section: Introductionmentioning
confidence: 99%